Determination of the U.S. Pleading from the Civil Law Perspective - Cesare Cavallini (Washington University Global Studies Law Review, 2022)
Determining the allegations of a pleading is still one of the most controversial topics in U.S. federal civil procedure law. As the Supreme Court’s statements in Twombly and Iqbal have spawned extensive literature, the purpose of this article is to address the matter from a different and to some extent, unusual, perspective, namely the provisions of the civil law pleading, analyzed in terms of their historical development and conceptual cornerstones. In seeking to go beyond a mere comparative analysis, this methodological approach aims to better understand the Supreme Court’s interpretation. In particular, this approach allows us to conduct what in the U.S. is often overlooked: a combined evaluation of both the policy considerations and the conceptual framework. While both informed the creation of the introductory phase within civil law systems, it should be noted that policy values were also prominent in shaping the 1938 Federal Rules of Civil Procedure, according to Clark’s general vision of civil justice at the time. This approach raises the question as to whether the Supreme Court has been the change-maker or whether the Supreme Court has unavoidably had to turn toward a stricter determination of pleadings, to accommodate the changing nature and needs of litigation. The answer to this daunting question is two-fold, and the historical and international comparison conducted strengthens the conclusion. First, the non-conclusory factual allegations, to be considered as true, perfectly align with the requirements of pleading within civil law systems. The essential role played by the claim within the different legal traditions converges not only at the definitory level; indeed, in both traditions, we might consider the requirements of the pleading as being the most critical step in defining the lawsuit’s subject matter and its res judicata binding effects. Second, managerial judging, as it notably finds fertile humus in the civil law, might serve to moderate hasty motions to dismiss and avoid the misunderstood gatekeeping function at the mere pleading stage.